Companies with potential to join the fourth industrial revolution listed in Brazil, Bolsa, Balcão (Research, Society and Development, 2020)
This article sought to present the main concepts of industry 4.0 and the fourth industrial revolution, as well as its importance for the world industry. Reinvestments in the company as a matter of seeking innovation and long-term survival is still a challenge for Brazilian companies. The aim of this article is to conduct a survey of industries that are listed in Brazil, Bolsa, Balcão (B3) and identify its possible adherence to the fourth revolution using the Pi formula as a matter of delimiting companies that can be insolvent and thus participate in the fourth industrial revolution in the future. The methodology used was a descriptive and quantitative research in a logistic regression using as a base publicly traded companies extracted from Capital IQ and Bloomberg. A study using econometric model was adopted to perform the calculations and the results show that only 10 industrial companies in a sample of 78 are reinvesting their profits in Capex, seeking technology innovation and consequently survive in the long run.